Chronic nasal exposure to nanoparticulate TiO2 causes pulmonary tumorigenesis in male mice. Issue 5 (19th January 2017) - Hong, Fashui; Ji, Li; Zhou, Yingjun; Wang, Ling
Abstract: Chronic inhalation bioassays in rodents are used to assess pulmonary carcinogenicity for purposes of hazard identification and potentially for risk characterization. Numerous studies have been confirmed that exposure to titanium dioxide nanoparticles (TiO2 NPs) may result in chronic pulmonary inflammation in both mice and rats. However, very few studies have focused on the pulmonary tumorigenesis. In this study, to examine whether chronic TiO2 NP exposure induce tumorigenesis in the lung, forty mice (each group) were nasally exposed to 1.25, 2.5, and 5 mg/kg body weight TiO2 NPs for nine consecutive months, lung pathology was then evaluated, and the biochemical function parameters in bronchoalveolar lavage (BAL) and tumor markers in the serum were investigated using an ELISA method. We observed that nasal exposure to TiO2 NPs caused infiltration of inflammatory cells, tumorigenesis in the lung, and accompanied by significant increases of lactate dehydrogenase, alkaline phosphatase, and total protein levels in BLAF, significant increases in tumor markers including cytokeratin 19, neuron‐specific enolase, carcinoembryonic antigen, squamous cell carcinoma antigen, and cancer antigen‐125 in the serum. It implies that chronic inhaled TiO2 NPs may increase possibility of pulmonary tumor formation for human. Therefore, the production and application of TiO2 NPs should be paid more attention. © 2016 Wiley Periodicals, Inc. Environ Toxicol 32: 1651–1657, 2017.